Is Medical Informatics an Art or a Science? - Haux, R.; Hasman, A.; McCray, A. T.; van der Lei, J. (Methods of Information in Medicine, 2006)
Objective: To give an introduction to the special topic on ‘Medical Informatics: Art or Sciene?‘ in honor of Prof. Dr. Jan Hendrik van Bemmel.Method: Retrospective, personal review on his work.Results and Conclusions: Jan H. van Bemmel contributed exceptionally to research and education as well as to systematizing and promoting medical informatics. Details are provided in this and the other papers of this special topic of Methods of Information in Medicine.
Keywords: Medical informatics; health informatics; biomedical informatics; research education